Economists, Research Performance and National Inbreeding: North Versus South. (19th August 2016) - Katranidis, Stelios; Panagiotidis, Theodore; Zontanos, Costas
Abstract : We investigate the research performance of 404 economists working in 17 Economics Departments and 4 countries. Two countries from the North of Europe (Belgium and Denmark) are compared with two countries from the South (Greece and Portugal) in terms of research productivity. Their performance is ranked using bibliometric indices. We examine the factors that drive economist's research performance using OLS and quantile regression analysis. The most productive economists have a US PhD and work in the North. Inbreeding at the national level is associated with higher productivity in the North and lower in the South.